A novel TRPS1 mutation in a family with tricho‐rhino‐phalangeal syndrome type 1. Issue 6 (June 2014) - Fujisawa, Tomomi; Fukao, Toshiyuki; Shimomura, Yutaka; Seishima, Mariko
Abstract Tricho‐rhino‐phalangeal syndrome (TRPS) is an autosomal‐dominant disease characterized by sparse and slow‐growing scalp hair and craniofacial and skeletal abnormalities. We report here the case of two girls and their father who had TRPS type 1 and received a diagnosis of a new mutation of TRPS1 based on their clinical symptoms. Moreover, histological studies on skin samples obtained from one of the patients showed enhanced signal transducers and activator of transcription (STAT) 3 expression in the outer root sheath. However, TRPS1 protein expression was not reduced in the patient's follicles. These findings indicate that truncated TRPS1 protein from the mutant allele may be stably expressed in the patient's follicles and that enhanced STAT3 expression may be involved in the development of sparse and thin scalp hair in TRPS.